Penilaian Kualitas Lingkungan Binaan Layak Huni Berdasarkan Aspek Fisik (Kasus: Kampung Warna Warni Jodipan, Malang) - Fidelista, Alya Nafisa; Nugroho, Agung Murti; Lisa Dwi Wulandari (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2024)
The study aims to rate and categorize the quality of the livable built environment in Kampung Warna-Warni Jodipan, which is a riverside settlement. It will do this by identifying important physical features through visual observation, visual interpretation of ArcGIS, scoring, and weighting. We use visual observation methods and visual interpretation of ARCGis to determine and evaluate physical conditions that impact the quality of the settlement environment. We use the scoring and weighting techniques to assess and classify the quality of the habitable built environment in Kampung Warna-Warni Jodipan. The results of this study show the physical aspects that form the quality of the residential environment affect the quality of the habitable built environment both positively and negatively. Physical aspects that have a good effect are the road surface and roof coverings of buildings; physical aspects that have a moderate effect are the density of buildings and settlement locations; while the physical aspects that adversely affect are the width of the driveway, protective trees, and building layout. The medium quality classification includes Kampung Warna-Warni Jodipan RW 2, RT 6, 7, and 9, with RT 7 having a poor classification value and RT 6 and 9 having a medium one.